A Narrative Review: Augmented Renal Clearance and Its Effect on Drug Therapy - Selamet, Ni Made Dwi Antika; Sari, Ika Puspita; Andayani, Tri Murti (Rumah Sakit Akademik Universitas Gadjah Mada, 2025)
Background: Augmented renal clearance (ARC) is a common condition in critically ill patients, particularly in intensive care units, characterized by enhanced renal elimination. The accelerated elimination of drugs can significantly impact therapeutic efficacy, potentially resulting in suboptimal treatment outcomes. This review aims to provide a comprehensive overview of drugs impacted by ARC, offering a better understanding of the impact of ARC on drug therapy.Method: A narrative review was conducted to explore previous studies from Scopus, PubMed, and ScienceDirect. PRISMA flow chart was used to guide the article selection process.Result: A total of 14 articles were comprehensively reviewed and discussed regarding drugs affected by ARC, the impact of ARC on the pharmacokinetic/pharmacodynamic properties of drugs, and their clinical outcomes. Classes of drugs affected by ARC include beta-lactam antibiotics, glycopeptide antibiotics, anticoagulants, and anticonvulsants.Conclusion: Antibiotics are the most frequently reported drugs to be impacted by ARC, followed by anticoagulants and anticonvulsants. The impact of ARC on anticoagulants is inconsistent. ARC reduces free drug concentration, requires a higher dose to achieve the therapeutic target, and is associated with a higher risk of treatment failure. However, no significant differences were found in clinical response and mortality compared to non-ARC.